Yemen National Food Security Strategy 7 Point Action Plan - Breisinger, Clemens (2013)
The 7-Point Action Plan was jointly developed by the Ministries of Planning and International Cooperation; Finance; Trade; Public Health and Population, Agriculture and Irrigation, Water and Environment; Fish Wealth, as well as the Social Welfare Fund, the Social Fund for Development, the Central Statistics Organization, and the International Food Policy Research Institute.